5G OPTIMIZATION: MATHEMATICAL MODELS, ALGORITHMS AND REALITY - Chermianin, Anton (Science-based technologies, 2025)
The purpose of this article is to provide a comprehensive overview of modern methods for optimizing fifth-generation (5G) networks using mathematical models and algorithms. The article presents an in-depth analysis of approaches aimed at enhancing the performance of 5G networks, with a focus on minimizing latency, ensuring high energy efficiency, and improving spectral efficiency—key parameters for meeting the demands of modern mobile services and mission-critical applications. The discussion covers theoretical methods such as linear and nonlinear programming, stochastic modeling, machine learning algorithms, and robust optimization techniques, which play a crucial role in designing effective solutions for dynamic and resource-constrained 5G environments. Despite significant progress made in recent years, numerous challenges remain before these technologies can be fully implemented in real-world commercial networks. One of the key issues is the gap between theoretical models, which often rely on simplifying assumptions, and the complex reality of mobile network operation, characterized by dynamic traffic patterns, unstable communication channels, and limited energy and computational resources, especially at the network edge. The article also addresses factors that limit the practical use of existing optimization algorithms, including high computational costs, data processing delays, and difficulties in scaling to large numbers of connected devices. To address these challenges, the article discusses promising research directions, including the integration of artificial intelligence, mobile edge computin), self-organizing networks, and hybrid optimization methods that combine the strengths of different approaches to achieve greater flexibility and adaptability. In particular, the implementation of decentralized control systems is considered promising, as they allow real-time responses to changes in the network environment. By gaining deeper insight into current challenges and technological opportunities, this article provides a valuable roadmap for future academic and applied research in 5G optimization. Continued exploration in the field of resource management—including efficient spectrum allocation, latency reduction, improved energy efficiency, and increased resilience to external influences—is critical for achieving stable, high-performance, and reliable operation of next-generation wireless networks, in line with the demands of the digital society and the evolution of Internet of Things, autonomous transport, and industrial automation technologies.